2003
DOI: 10.1021/es0259685
|View full text |Cite
|
Sign up to set email alerts
|

Soil Wettability As Determined from Using Low-Field Nuclear Magnetic Resonance

Abstract: The molarity of ethanol droplet and water drop penetration time methods are commonly used to determine soil wettability because these tests are quick and easy to perform. However, these tests do not provide reproducible results on the same sample. Low-field nuclear magnetic resonance (NMR) is shown as an alternative tool to determine soil wettability. Addition of small amounts of water in dry wettable porous media produces predominant amplitude peaks at transverse relaxation times (T2) of 100 ms or less while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…The positions of the peaks in the T 2 relaxation spectrum have been used to determine the wettability, wettability alteration and water uptake of soil and sand cores [21,61]. Water in preferentially water-wet samples was shown to have T 2 peaks around 100 ms or less.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The positions of the peaks in the T 2 relaxation spectrum have been used to determine the wettability, wettability alteration and water uptake of soil and sand cores [21,61]. Water in preferentially water-wet samples was shown to have T 2 peaks around 100 ms or less.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…They found that water relaxed faster in the water-wet system than in the oil-wet system. Later works (Devereux, 1967;Saraf et al, 1970;Williams and Fung, 1982;Borgia et al, 1991;Hsu et al, 1992;Howard, 1994;Straley et al, 1995;Daughney et al, 2000;Zhang et al, 2000;Al-Mahrooqi et al, 2003;Manalo et al, 2003) confirm that NMR technique can give qualitative information about wettability. However, the quantitative connection between wettability and NMR characteristic parameter has been investigated by only a few studies (Howard, 1998;Guan et al, 2002;Fleury and Deflandre, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…They also showed signs of a possible swelling of organic matter and of changes of the relaxation times of water during the first days of swelling. Langford et al (2002), Manalo et al (2003) and Todoruk et al (2003a, b) used H-NMR-Relaxometry to determine and understand soil wettability. A detailed discussion of their NMR data would be of particular relevance, because appropriate independent validation methods are not yet available.…”
Section: Swelling Of Sommentioning
confidence: 99%